The Synchronization of Hindu Buddhist Spatial and Architecture in Traditional Javanese Mosques - Pratiwi, Yulia; Numan, Ibrahim; Cholis Idham, Noor (Journal of Architectural Research and Design Studies, 2024)
The architecture and space in traditional Javanese mosques are synchronized with previous religions and cultures. Islamization takes the form of synchronization, acculturation, syncretism, adaptation and adoption by Traditional Javanese Mosques of animistic beliefs, dynamism, Hindu Buddhism, and Javanese culture. This research is unique because it compares traditional Javanese mosques with Hindu Buddhist buildings in the form of temples. This research aims to examine the synchronization of animism, dynamism, Hinduism, Buddhism, and Javanese towards the architecture and space of traditional Javanese mosques in three elements. The first element is spatial systems such as land use and vegetation. The second element is the physical system which includes building form and massing, roof, and gate. The last element is the stylistic system, especially for outdoor ornaments. The research method used compares Hindu Buddhist buildings and artifacts in Indonesia and traditional Javanese mosques. The conclusions are there are a synchronization of spatial elements in vegetation, synchronizations of physical elements in roofs and gates, and synchronizations of stylistic elements in the gate ornaments synchronized from Kala to floral motifs. Keywords: islamization; mosque; space; vernacular architecture